2006
DOI: 10.1063/1.2405874
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet broadband Mo∕Y multilayer analyzers

Abstract: Broadband extreme ultraviolet molybdenum/yttrium aperiodic multilayer analyzers were designed for polarization experiments in 8.5-11.7 nm wavelength range. The multilayer analyzers were made using direct current magnetron sputtering and characterized using the soft x-ray polarimeter at BESSY-II facility. Measured s reflectivities at the Brewster angle are 5.5% for a multilayer designed for 8.5-10.1 nm wavelength range and 6.1% for one designed for 9.1-11.7 nm. The multilayers also exhibit high polarization deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 20 publications
1
27
0
2
Order By: Relevance
“…49 The polarization degree or phase shift has to be taken into account in the merit function during multilayer design to achieve the broadband effect. [50][51][52] A high polarization degree of up to 98.7% with an average reflectance for s-polarized light of 5.5% to 6.1% has been demonstrated over the wavelength range of k ¼ 8.5-11.7 nm by Wang et al An aperiodic Mo/Y multilayer was used in this experiment and the results are shown in Figure 4. 52 A multilayer transmission phase retarder with 42 phase shift in the range of k ¼ 13.8-15.5 nm was also realized using Mo/ Si multilayers.…”
Section: Broadband Multilayer Polarizermentioning
confidence: 98%
See 1 more Smart Citation
“…49 The polarization degree or phase shift has to be taken into account in the merit function during multilayer design to achieve the broadband effect. [50][51][52] A high polarization degree of up to 98.7% with an average reflectance for s-polarized light of 5.5% to 6.1% has been demonstrated over the wavelength range of k ¼ 8.5-11.7 nm by Wang et al An aperiodic Mo/Y multilayer was used in this experiment and the results are shown in Figure 4. 52 A multilayer transmission phase retarder with 42 phase shift in the range of k ¼ 13.8-15.5 nm was also realized using Mo/ Si multilayers.…”
Section: Broadband Multilayer Polarizermentioning
confidence: 98%
“…56,57 The latter one is based on the different penetration depth inside the multilayer for different frequency components of the incoming light, so that a negative or positive chirp can be achieved to compensate the intrinsic chirp among the harmonics and further compress the pulse. 55,58 Based on this idea, aperiodic chirped multilayers were first designed with 52 the desired phase characteristics and for these designs an attosecond-level pulse duration was predicted. 57,59 With the advancement of the deposition techniques and various methods of phase measurements, significant progress has been achieved in chirped multilayer mirrors over the past few years.…”
Section: Broadband Multilayer For High Temporal Resolutionmentioning
confidence: 99%
“…Broadband transmission measurements demonstrated that the grown BP films have a broad absorption band from 130 eV to 300 eV, as a result of the overlapping P L 2,3 , P K and B K absorption edges. This work shows that, through c-BP, the P L 2,3 -edge can in principle be employed to construct optical elements that are relatively transparent to photons with an energy below 130 eV, which can be applied in space optics [19,20], photolithography [21] and high harmonics generation [22].…”
Section: Introductionmentioning
confidence: 99%
“…We mainly focus on the properties of phosphorus-based multilayer mirrors operating at around the L 2,3 absorption edge of phosphorus (P). Reflective optics operating at around the photo absorption edge of P is of interest for several applications, including extreme ultraviolet astronomy [4][5][6][7] and high-harmonic generation [8,9]. Here we theoretically examine reflective properties of planar multilayer structures with BP spacer and different reflector materials that suggest high reflectivity values.…”
Section: Introductionmentioning
confidence: 99%